Band-limited noise interference in loudspeaker systems - T. FIDECKI (Archives of Acoustics, 2014)
It is often argued that the interference of sound from distant loudspeakers is negligible in the case of band-limited noise. Simple theory and experiment in a reflection-free environment with a pair of loudspeakers radiating a third-octave noise proves that in the case of coherent supply SPL variations are considerable. The variations disappear when non-coherent signal is applied indicating that non-coherent supply of loudspeakers is necessary wherever approximation of diffuse sound field is required.